2018
DOI: 10.3892/ol.2018.7851
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine regulates breast cancer cell viability, migration, invasion and apoptosis by affecting the activity of Akt and caspase-3

Abstract: Abstract. Tetramethylpyrazine (TMP), an effective component of the traditional Chinese medicine Chuanxiong Hort, has been proven to exhibit a beneficial effect in a number of types of malignant epithelial cancer. However, the mode of action of TMP on breast cancer cells remains unknown. The aim of the present study was to investigate the regulatory effect of TMP on breast cancer cells and its underlying molecular mechanism of action. Different concentrations of TMP were used to treat breast cancer cells, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…The results revealed that 8e could induce FaDu cells' apoptosis in a dose-dependent manner. This was consistent with other reports showing TMP and its derivatives could induce apoptosis of cancer cells [22][23][24].…”
Section: Apoptosis Analysis By Annexin V-fitc/pi Stainingsupporting
confidence: 94%
“…The results revealed that 8e could induce FaDu cells' apoptosis in a dose-dependent manner. This was consistent with other reports showing TMP and its derivatives could induce apoptosis of cancer cells [22][23][24].…”
Section: Apoptosis Analysis By Annexin V-fitc/pi Stainingsupporting
confidence: 94%
“…There are reports that show Chuanxiong (Ligusticum chuanxiong) and Danggui (Angelica sinensis) also can exert anti-tumor effects. Shen J et al [14] used RT-qPCR and western blot analysis to show that CX signi cantly decreased the Akt expression and activity, increased the activity of caspase-3, and was also shown to have anti-tumor effects in several types of cancer. DG can induce gastric cancer cell death through inhibiting mTOR protein and can signi cantly prolong the survival rate of cancer patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…It has been generally recognized that traditional Chinese herbal medicines played a unique therapeutic role in the treatment of many diseases (Bhamra et al, 2017;Perry et al, 2018;Li et al, 2019). Tetramethylpyrazine (TMP), an effective component of the traditional Chinese medicine Chuanxiong Rhizoma, which has been used to treat cerebrovascular and cardiovascular diseases, pulmonary diseases and cancer (Huang et al, 2018;Shen et al, 2018). And it was reported that TMP could ameliorate fibrosis in myocardial pulmonary and liver (Wu et al, 2015;Wang et al, 2017;Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%